The Influence of Principal’s Leadership and Teacher’s Competence toward Teacher’s Performance in Indonesia - Suratman, Suratman; Arafat, Yasir; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2020)
This study determined whether there is an effect of principal leadership and teacher competence on teacher’s performance at SMP Negeri 1 Sungai Lilin, either partially or simultaneously. The population of this research is 40 teachers. The technique of collecting data using a questionnaire, with data analysis using multiple linear regression of SPSS 25. The results obtained in this study 1) there is no influence of principal leadership on teacher’s performance; 2) there is an effect of teacher’s competence on teacher’s performance; and 3) simultaneously there is an effect of principal leadership and teacher’s competence on teacher’s performance. This paper contributes to improve teacher’s performance through principal leadership and teacher’s competence.